Field investigation of grout propagation within a caving mass under flowing water conditions in a metal mine - Baofu Wu; Guilei Han; Zhiqi Wang; Jiabin Shi; Hongjiang You; Asrullah (Deep Underground Science and Engineering)
Abstract Due to the invisibility and complexity of the underground spaces, monitoring the propagation and filling characteristics of the grouting slurry post the water–sand mixture inrush in metal mines is challenging, which complicates engineering treatment. This research investigated the propagation law of cement‐sodium silicate slurry under flowing water conditions within the caving mass of a metal mine. First, based on borehole packer test results and borehole TV images, the fractured strata before grouting were classified into four types: cavity, hidden, fissure, and complete. Second, an orthogonal experimental design was employed to evaluate the impact of four key factors—stratigraphic fragmentation, water flow rate, grouting flow rate, and water‐cement ratio—on the efficacy of grouting within a caving mass at the site. The results indicate that the factors influencing grouting efficacy are ranked in the following order of importance: stratigraphic fragmentation > water flow rate > water–cement ratio > grouting flow rate. Ultimately, five propagation filling modes—pure slurry, big crack, small crack, small karst pore, and pore penetration—were identified by examining the propagation filling characteristics of slurry in rock samples, incorporating microscopic material structure analysis through scanning electron microscopy and energy spectrum analysis. The findings of this study provide valuable insights into selecting engineering treatment parameters and methodologies, serving as a reference for preventing and controlling water–sand mixture inrush in metal mines, thereby enhancing treatment efficacy and ensuring grouting success.